Investigation on Positive Correlation of Increased Brain Iron Deposition with Cognitive Impairment in Alzheimer Disease by Using Quantitative MR R2＇ Mapping - 覃媛媛 朱文珍 占传家 赵凌云 王建枝 田青 王伟 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
Brain iron deposition has been proposed to play an important role in the pathophysiology of Alzheimer disease（AD）.The aim of this study was to investigate the correlation of brain iron accumulation with the severity of cognitive impairment in patients with AD by using quantitative MR relaxation rate R2＇ measurements.Fifteen patients with AD,15 age-and sex-matched healthy controls,and 30 healthy volunteers underwent 1.5T MR multi-echo T2 mapping and T2＊ mapping for the measurement of transverse relaxation rate R2＇（R2＇=R2＊-R2）.We statistically analyzed the R2＇ and iron concentrations of bilateral hippocampus（HP）,parietal cortex（PC）,frontal white matter（FWM）,putamen（PU）,caudate nucleus（CN）,thalamus（TH）,red nucleus（RN）,substantia nigra（SN）,and dentate nucleus（DN） of the cerebellum for the correlation with the severity of dementia.Two-tailed t-test,Student-Newman-Keuls test（ANOVA） and linear correlation test were used for statistical analysis.In 30 healthy volunteers,the R2＇ values of bilateral SN,RN,PU,CN,globus pallidus（GP）,TH,and FWM were measured.The correlation with the postmortem iron concentration in normal adults was analyzed in order to establish a formula on the relationship between regional R2＇ and brain iron concentration.The iron concentration of regions of interest（ROI） in AD patients and controls was calculated by this formula and its correlation with the severity of AD was analyzed.Regional R2＇ was positively correlated with regional brain iron concentration in normal adults（r=0.977,P0.01）.Iron concentrations in bilateral HP,PC,PU,CN,and DN of patients with AD were significantly higher than those of the controls（P0.05）;Moreover,the brain iron concentrations,especially in parietal cortex and hippocampus at the early stage of AD,were positively correlated with the severity of patients＇ cognitive impairment（P0.05）.The higher the R2＇ and iron concentrations were,the more severe the cognitive impairment was.Regional R2＇ and iron concentration in parietal cortex and hippocampus were positively correlated with the severity of AD patients＇ cognitive impairment,indicating that it may be used as a biomarker to evaluate the progression of AD.